2013
DOI: 10.1093/humrep/det307
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status affects the prevalence, but not the perinatal outcomes, of in vitro fertilization pregnancies

Abstract: None of the authors received any funding specifically for this study, and we have no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 21 publications
1
42
1
Order By: Relevance
“…Furthermore, it might be speculated that a part of SES disparity in giving birth by CS might be explained by differences in delivery training. The results of the present study contradicted those obtained in previous studies, which indicated inequity in both the access to healthcare and healthcare services offered, with a positive social gradient in IVF services [21] and cardiac procedures [19,20] in Finland.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it might be speculated that a part of SES disparity in giving birth by CS might be explained by differences in delivery training. The results of the present study contradicted those obtained in previous studies, which indicated inequity in both the access to healthcare and healthcare services offered, with a positive social gradient in IVF services [21] and cardiac procedures [19,20] in Finland.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, women with the highest SES were more likely to undergo in vitro fertilization in Finland [21-23]. In Finland, practically all pregnant women give birth in public hospitals with free-access, and private delivery care services are not provided.…”
Section: Introductionmentioning
confidence: 99%
“…This could be because nulliparous women with placenta previa were less likely to be smokers in our study, and no significant association was noted in multiparous women. Many nulliparous women conceived by IVF and were ofhigh SES, older and less likely to smoke (18). …”
Section: Discussionmentioning
confidence: 99%
“…Here, it is speculated that women with gestational diabetes be advised to control their weight gain by their care providers during prenatal care. Conversely, women who conceive using ART tend to be of higher socioeconomic status and are more invested in their pregnancy . As a result, they could have monitored their weight gain more closely and have made necessary adjustment to better maintain their weight gain compared with women who conceived naturally.…”
Section: Discussionmentioning
confidence: 99%